If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 112 + -4x = 14x + 24 Reorder the terms: 112 + -4x = 24 + 14x Solving 112 + -4x = 24 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. 112 + -4x + -14x = 24 + 14x + -14x Combine like terms: -4x + -14x = -18x 112 + -18x = 24 + 14x + -14x Combine like terms: 14x + -14x = 0 112 + -18x = 24 + 0 112 + -18x = 24 Add '-112' to each side of the equation. 112 + -112 + -18x = 24 + -112 Combine like terms: 112 + -112 = 0 0 + -18x = 24 + -112 -18x = 24 + -112 Combine like terms: 24 + -112 = -88 -18x = -88 Divide each side by '-18'. x = 4.888888889 Simplifying x = 4.888888889
| H+6=3h | | 1.2-4.3=1.7 | | 2x+x+x-6=10 | | 7(3+4)= | | -11x^2+5=6x | | y^2-16y-80=0 | | 0=x^2+10x+5 | | 10x-8x-1=5+2+3 | | -12*-2= | | 7(x-8)=3(x+4) | | -27x^2+6x=0 | | 0.25(4+20r)-8=-5 | | 4(8-5x)=-2x-4 | | 10x+2x-8=40 | | 3(x+8)=7x | | 7(x+2)=40 | | 4(2.5)+3x=15.25 | | 4-3(2x-3)+5x=10+7(3x+2) | | 93-2x=4x+21 | | -10n^2+13n-18=(-9n+3)(n-2) | | 11x-23=12x+5 | | (y-13)20= | | 17+3x=5x+3 | | 45-q=3(q-5) | | 6x+5=87 | | 6x+4x+5=80+5 | | 5(12-c)= | | -11x-5x=-10x | | 2x-3=7-2(2x-19) | | 5x-9=11x+5 | | -14(j+3)= | | x^2=10x-20 |